Sistem Informasi Akuntansi Pembelian Pada Pt. Antakesuma Inti Raharja di Surabaya (Laporan Kegiatan Kuliah Kerja Lapangan) - Aulia Isnaini Hasanah; Sutini Sutini; Heri Toni; Diana Zuhro; Tjandra Wasesa; Wiratna Wiratna (Universitas 45 Surabaya, 2023)
In the era of globalization like today, accounting information is a very valuable resource for a company. Information is needed to overcome competition in the business world. Important information needed is information that is strategic in nature, meaning information related to the long-term life of the company that is used as logical decision making and leads to the desired action. This situation requires the company to be more active and productive in running its business. Therefore, good and organized internal control is needed. One important factor that must be considered by companies is the purchase accounting information system. According to Mulyadi (2016: 3) the accounting system is an organization of forms, records and reports that are coordinated in such a way as to provide financial information needed by management in management. Accounting information systems have a very important role in companies to be competitive. Accounting information systems can assist managers in providing information and support in decision making and other policies.